Strategic positioning previous and posterior to the Covid-19 pandemic: a case study in a commercial air conditioner company in Brazil (Research, Society and Development, 2020)
Brazil, a country with a tropical climate, where due to high temperatures, there is an important thermal discomfort. Achieving a reduction in ambient temperature, ensures people a feeling of greater comfort. The Brazilian market, due to its population size of approximately 200 million inhabitants, generates a very large market in air conditioning systems; being the air conditioner, a product that has been gaining market due to its ease of installation, low cost and reduced consumption of electricity. Few academic studies address the strategic aspects of companies that sell air conditioners in Brazil; this research has as its general objective to analyze the strategic positioning of a company in the sector that sells products imported from China, and as a complementary objective to carry out a comparative strategic analysis before and after the pandemic Covid-19. Methodologically we have a case study unique, non-probabilistic and intentional, for convenience, exploratory and qualitative; data collection takes place through interviews, visits to the company, consultation of management accounting documents; it uses the techniques of Swot Analysis and Porter's Five Forces, and from the collected data a Content Analysis is elaborated. The limitations of the research are: single case study, and the difficulty in applying it to other companies; however, important academic contributions are highlighted. Finally, new lines of research emerge from the work, in understanding consumer behavior, in this new product that is consolidated in the Brazilian market and also the competitive mechanisms between companies in the sector.